If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 7(x + -8) = 9 + -3(x + -4) Reorder the terms: 4 + 7(-8 + x) = 9 + -3(x + -4) 4 + (-8 * 7 + x * 7) = 9 + -3(x + -4) 4 + (-56 + 7x) = 9 + -3(x + -4) Combine like terms: 4 + -56 = -52 -52 + 7x = 9 + -3(x + -4) Reorder the terms: -52 + 7x = 9 + -3(-4 + x) -52 + 7x = 9 + (-4 * -3 + x * -3) -52 + 7x = 9 + (12 + -3x) Combine like terms: 9 + 12 = 21 -52 + 7x = 21 + -3x Solving -52 + 7x = 21 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -52 + 7x + 3x = 21 + -3x + 3x Combine like terms: 7x + 3x = 10x -52 + 10x = 21 + -3x + 3x Combine like terms: -3x + 3x = 0 -52 + 10x = 21 + 0 -52 + 10x = 21 Add '52' to each side of the equation. -52 + 52 + 10x = 21 + 52 Combine like terms: -52 + 52 = 0 0 + 10x = 21 + 52 10x = 21 + 52 Combine like terms: 21 + 52 = 73 10x = 73 Divide each side by '10'. x = 7.3 Simplifying x = 7.3
| 1-4y=1 | | -14=-4+5x+3x | | 33m-14+14=33 | | x-7=34-7(x+7) | | 4x-1=113 | | 124-v=185 | | -7+3y=-16 | | 16+8y=80 | | 4v-4=-24 | | 2(x-4)-3=7-4x | | 3=(-6)+x | | -5p=0 | | -x-10y=-24 | | 56=2(15)+2w | | -2y+30=5y-5 | | 3x+5x+-4=-14 | | 5+2*[3(x+5)-(3x+11)]=11-4x | | 3x+3x+4x+2x= | | 2-4d=0 | | 3y-5t+10=36 | | -5/9y25 | | y=1E+06X+17211 | | 10u-3u=42 | | (X-2)2+(y+5)2=12 | | 69x+13=151 | | -30=5+5y | | 5x*y=2720 | | p/3=2p/3=1/4 | | 7x+20y=18 | | 28=m/7=43 | | Fx=4x^2+4x-15 | | c-5/9(50-32)= |